The clinical Erich Fromm : personal accounts and papers on therapeutic technique (Rodopi, 2009)
"Rainer Funk's edited book is immensely valuable because it presents Fromm's clinical ideas and clinical style through the voice of his supervisees, students, colleagues, and friends. Funk's book provides a timely and important addition to our understanding of Fromm. It fills a gap in the secondary literature by demonstrating the way in which Fromm was an especially skillful and talented clinician, in addition to being a writer of great renown. By offering first-hand accounts of their work with Fromm, the contributors help readers to grasp how the "clinical Erich Fromm" worked in his psychoanalytic practice and how he conceptualized clinical case material. In the process, Funk's book deepens our appreciation of Fromm as a thinker, clinician, and a human being. Most importantly, this book illustrates the wealth of Fromm's approach, and picks it up at the moment when psychoanalytic psychotherapy is confronting a challenge to its whole way of thinking and practicing. It reveals how Fromm's therapeutic approach, which emphasizes direct encounter with the patient and values the contextualization of experience, remains directly relevant for the changing culture of contemporary psychotherapy."--Roger Frie, Associate Professor, Simon Fraser University and Faculty, William Alanson White Institute.
Description based upon print version of record.
Keywords: Psychoanalysis.; Fromm, Erich, -- 1900-1980.